Ensaios sobre a “Lei de Aprendizagem” brasileira: efeitos sobre a contratação de jovens, mobilidade ocupacional, reinserção laboral e diferencial de salários - Nunes, Erivelton de Souza (2024)
The Brazilian Apprenticeship Law, promulgated by Law 10.097/2000 and regulated by Decree 5.598/2005, aims to facilitate the transition of young people into their first jobs through professional training, and to increase their specific human capital for future wage gains. It establishes a quota of apprentices of at least 5% and a maximum of 15% of the regular workforce of medium and large companies. However, the Law has generated both positive and negative effects. On one hand, it contributes to increased formality, reduced turnover, and growth in wages for young people willing to work. On the other hand, it has not stimulated the accumulation of specific human capital or the retention of apprentices in the same training company, and it has not been satisfactorily enforced. Thus, considering the unsatisfactory compliance with the Apprenticeship Law, its limited encouragement of specific human capital accumulation, and the inverse relationship between low accumulation of specific human capital and occupational mobility, as well as the influence of mobility on wage differentials, this Thesis aims to construct two chapters. In the first, the effect and effectiveness of the "Apprenticeship Law" on the hiring of young apprentices in Brazil are evaluated. In the second, the effect of the "Apprenticeship Law" on the income differential among Brazilian young apprentices is analyzed, considering occupational mobility and labor reintegration. To this end, regression discontinuity methods with fuzzy and sharp approaches are used, and a decomposition method through the unconditional quantile approach based on the Re-centered Influence Function (RIF) is employed. Microdata from the Annual Social Information Report (RAIS) for the periods 2006-2019, in the case of the first chapter, and 2005-2019, for the second chapter, are utilized. The results suggest that, despite the increasing trend in the number of establishments participating in the apprenticeship program during the study period, it remains small: the percentage of employers in compliance with the Young Apprentice Law varied from 2.42% in 2006 to 26.91% in 2019. It is also evident that apprenticeship hiring by establishments in the Commerce and Services, and the Industry and Construction sectors, falls short of the quota, suggesting the introduction of control and monitoring mechanisms to increase the effectiveness of the Law. Furthermore, it was also observed that occupational mobility and labor reintegration generate income gains. Among the main factors associated with these results are the encouragement of career progression by the apprenticeship program and the promotion of learning up to the so-called reservation wage. The results also confirm that the Brazilian apprenticeship program contributes little to the accumulation of specific human capital. Thus, the low compliance with the Law requires greater oversight and monitoring. Analyses related to income differentials in occupational mobility and labor reintegration indicate the need for a greater effort in the theoretical and practical professional learning of young people, to ensure that economic gains associated with the apprenticeship experience are assured.